The Thermo-Optical Treatment of Cancer by Laser Light with Ag Nanoparticles - HasanTuhmaz H. (University of Thi-Qar Journal of Science, 2020)
In this paper, the photo thermal treatment of cancer with Ag nano- particles is studied. The PTT for tissue under the effect of heat by laser source with injection of silver nano- particles on the affected area. Bio-heat equation is solved by the numerical simulation methods. Results are summarized in the effect on the increasing of temperature at different time durations. These results are looked that the depth penetration of laser that lead to increasing heat raising during the increasing the time duration of exposure. Then, it estimated the peak value of depth on limited temperature.